Pengaruh Holding Time (Waktu Tahan) Dan Variasi Media Quenching (Pendinginan) Terhadap Nilai Kekerasan Baja Karbon Rendah ST 42 Pada Proses Pengkarbonan Padat Menggunakan Arang Batok Biji Pala (Myristica fagrans) - Krist - Waas (JURNAL SIMETRIK, 2020)
The purpose of this study was to obtain the hardness value of each variation of holding time and the variation of quenching medium (cooling) used. So we can compare the change in hardness value obtained and then can determine the retaining time as well as a good quenching medium to increase the hardness value of low carbon steel. The method used in this study is an experimental method. With a low carbon steel sample of ST 42 plate shaped as much as 26 pieces was done hardness testing before and after solid carburization process. Hardness testing is done by Rockwell B (HRB) method. The process of carburizing (pack carburizing), carried out at 950OC temperature with holding time is 1 hour, 2 hours, 3 hours and 4 hours. The results of this study indicate that the cooling medium which has a fast cooling rate of water media. While the seawater cooling medium can increase the hardness value of low carbon steel.